MENINGKATKAN HASIL BELAJAR PENDIDIKAN KEWARGANEGARAAN (PKN) MELALUI METODE KOPERATIF ROTATING TRIO EXCHANGE (RTE) PADA SISWA KELAS IV DI SD NEGERI 70 KOTA TERNATE - Tawari, Iswan E (Program Studi Pendidikan Ekonomi Institut Sain dan Kependidikan (ISDIK) Kie Raha Maluku Utara, 2025)
Improving Civic Education (Pkn) Learning Outcomes Through Cooperative MethodsRotating Trio Exchange (Rte)In Grade IV Students at State Elementary School 70, Ternate City, Ternate Institute of Science and Education (Isdik) Kie Raha North Maluku.This study aims to improve the learning outcomes of Civic Education (PKn) of fourth grade students of SD Negeri 70 Ternate City through the application of learning models.Rotating Trio Exchange (RTE). The problem of low interest and learning outcomes in Civics is caused by less innovative and monotonous learning methods. This Classroom Action Research (CAR) was conducted in two cycles, with 20 fourth-grade students of Gita State Elementary School as subjects in the 2025/2026 academic year.The results of the study showed a significant increase in student activity and learning outcomes. In Cycle I, student activity was in the